VD_FINDINFO HC / 2014 / 749 vom 23. September 2014 - VD Tribunal cantonal (2014)
RADIATION DU RÔLE, RETRAITVOIE DE DROIT, DEMANDE ADRESSÉE À L'AUTORITÉ, RÉVISIONDÉCISION | 241 al. 3 CPC (CH), 11 TFJC (2010)